Electromechanical factors associated with favourable outcome in cardiac resynchronization therapy. Issue 2 (15th September 2022) - Maffessanti, Francesco; Jadczyk, Tomasz; Wilczek, Jacek; Conte, Giulio; Caputo, Maria Luce; Gołba, Krzysztof S; Biernat, Jolanta; Cybulska, Magdalena; Caluori, Guido; Regoli, François; Krause, Rolf; Wojakowski, Wojciech; et al.
Abstract: Aims: Electromechanical coupling in patients receiving cardiac resynchronization therapy (CRT) is not fully understood. Our aim was to determine the best combination of electrical and mechanical substrates associated with effective CRT. Methods and results: Sixty-two patients were prospectively enrolled from two centres. Patients underwent 12-lead electrocardiogram (ECG), cardiovascular magnetic resonance (CMR), echocardiography, and anatomo-electromechanical mapping (AEMM). Remodelling was measured as the end-systolic volume (ΔESV) decrease at 6 months. CRT was defined effective with ΔESV ≤ −15%. QRS duration (QRSd) was measured from ECG. Area strain was obtained from AEMM and used to derive systolic stretch index (SSI) and total left-ventricular mechanical time. Total left-ventricular activation time (TLVAT) and transeptal time (TST) were derived from AEMM and ECG. Scar was measured from CMR. Significant correlations were observed between ΔESV and TST [rho = 0.42; responder: 50 (20–58) vs. non-responder: 33 (8–44) ms], TLVAT [−0.68; 81 (73–97) vs. 112 (96–127) ms], scar [−0.27; 0.0 (0.0–1.2) vs. 8.7 (0.0–19.1)%], and SSI [0.41; 10.7 (7.1–16.8) vs. 4.2 (2.9–5.5)], but not QRSd [−0.13; 155 (140–176) vs. 167 (155–177) ms]. TLVAT and SSI were highly accurate in identifying CRT response [area under the curve (AUC) > 0.80], followed by scar (AUC > 0.70). Total left-ventricular activation time (odds ratio = 0.91), scar (0.94), and SSI (1.29) were independent factors associated with effective CRT. Subjects with SSI >7.9% and TLVAT <91 ms all responded to CRT with a median ΔESV ≈ −50%, while low SSI and prolonged TLVAT were more common in non-responders (ΔESV ≈ −5%). Conclusion: Electromechanical measurements are better associated with CRT response than conventional ECG variables. The absence of scar combined with high SSI and low TLVAT ensures effectiveness of CRT. Graphical Abstract: Graphical Abstract